The Use of Stripe Movie With Scientific Aproach to Increasing Activity and History Learning Result to Student Class XII IPS 2 SMAN 3 Jember, Academic Year 2016/2017 - Eka Oktaviana; Sumardi Sumardi; Sumarno Sumarno (JURNAL HISTORICA, 2017)
Learning history is expected to motivate the students to build their own historical story (to visualize historical events of history) by themselves based on existing facts. The learning process is also expected could push the students in finding new knowledge through their own consideration which supported by the appropriate learning strategy until the students could actively participate in learning history. The goal of this research is to analyze the activity and the result of learning history by applied learning media of stripe movie supported by a scientific approach to the students of class XII IPS 2 in SMAN 3 Jember academic year 2016/2017. The subject of this research is 29 students of class XII IPS 2 in SMAN 3 Jember. The result of this research shows that in every step, the activity and the result of study increase. From five indicators the increasing of the 1st cycle to the 2nd cycle is 6,08%, the increasing of the 2nd cycle to the 3rd cycle is 5,73%. The score of 1st cycle activity classically is 59,84%, the 2nd cycle is 63,10%, and the 3rd cycle is 66,72%. Meanwhile, the increasing of the result of the study the 1st cycle to the 2nd cycle is 2,39%, and the 2nd cycle to the 3rd cycle is 3,59%. Classically, the score of the result of a study in the is 1st cycle 74,89%, the 2nd cycle is 76,68%, and the 3rd cycle is 79,44%. The conclusion of this research is the using of the learning media stripe movie that is supported by the scientific approach could increase the activity and the result of learning history to the students of class XII IPS 2 in SMAN 3 Jember academic year 2016/2017. Keywords: the learning media stripe movie, activity, the result of study